Three aromatic residues are required for electron transfer during iron mineralization in bacterioferritin - Bradley, JM; Svistunenko, DA; Lawson, TL; Hemmings, AM; Moore, GR; Le Brun, NE (Wiley, 2015)
Ferritins are iron storage proteins that overcome the problems of toxicity and poor bioavailability of iron by catalyzing iron oxidation and mineralization through the activity of a diiron ferroxidase site. Unlike in other ferritins, the oxidized di-Fe3+ site of Escherichia coli bacterioferritin (EcBFR) is stable and therefore does not function as a conduit for the transfer of Fe3+ into the storage cavity, but instead acts as a true catalytic cofactor that cycles its oxidation state while driving Fe2+ oxidation in the cavity. Herein, we demonstrate that EcBFR mineralization depends on three aromatic residues near the diiron site, Tyr25, Tyr58, and Trp133, and that a transient radical is formed on Tyr25. The data indicate that the aromatic residues, together with a previously identified inner surface iron site, promote mineralization by ensuring the simultaneous delivery of two electrons, derived from Fe2+ oxidation in the BFR cavity, to the di-ferric catalytic site for safe reduction of O2.